Words to live by : (Japan Publishing Industry Foundation for Culture, 2018)
Mountain/Home presents new translations of Japanese literature from the country’s medieval period to the present. The narrative arc of the selections follows the evolution of Japan’s national self-image. Because Mount Fuji, more than any other national symbol, has represented the soul of Japan, Mountain/Home begins with works inspired by the mountain’s presence. They include excerpts from some of the first literary works in which Mount Fuji appears: the mysterious Tale of the Bamboo Cutter, early court poetry, and the Confessions of Lady Nijо̄, among others. These works are followed by a chapter from Lady Murasaki’s brilliant novel, The Tale of Genji, and Edo-period haiku by Bashо̄ and Issa. In the twentieth century, Japan went through its darkest years. But out of the trauma of militarism, war, devastation, and defeat came outstanding fiction by Dazai Osamu and Natsume Sо̄seki, as well as avant-garde poetry by Yoshioka Minoru and Ayukawa Nobuo.